Management of children with obesity at local hospital and impact of COVID-19 pandemic - Ninchoji, Takeshi; Aoto, Yuya; Momo, Natsuki; Maruyama, Jun; Ioi, Hiroaki; Uchida, Hayato (Frontiers in Pediatrics, 2023)
This study investigated the status of children with obesity before and after the COVID-19 pandemic, and the effects of lifestyle guidance on weight loss among children in Japan. We analysed the data of patients who visited our hospital after check-ups for obesity and evaluated the efficacy of lifestyle guidance. The patients were divided into groups A, B, and C (year 2011, 2019, and 2021, respectively). There were no differences in body weight, obesity index (OI), blood pressure, or alanine transaminase (ALT) levels between the groups; however, aspartate transaminase (AST) level was the highest in Group C. In Group C, only OI increased between the primary and secondary screenings; however, OI and body mass index (BMI) improved during the second screening and more children in the weight loss group followed lifestyle guidance. OI/BMI did not change over the past decade; however, short-term weight gain was significant owing to the COVID-19 pandemic, and simple guidance was effective in reducing weight. Future challenges include identifying methods to achieve long-term weight loss.